Improving quality of life for women with incurable fistula in Uganda - Tripathi, Vandana; Emasu, Alice; Arnoff, Elly; Mukisa, Rose; Kanakulya, Hassan; Kirya, Fred (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To understand whether reintegration services can improve quality of life (QoL) for women with incurable fistula (WIF) in Uganda. Methods: Standardized tools measuring health/psychosocial status and QoL were administered before and after intervention to assess impacts: Self-Reporting Questionnaire (SRQ-20), WHO QoL-BREF, and modified King’s Health Questionnaire (KHQ). Results: Before intervention, all participants had SRQ-20 scores >8, indicating psychological distress. After intervention, there was significant reduction (to 37%) in the proportion of participants with scores indicating distress (p=0.0003). As measured by WHO QoL-BREF, self-reported QoL and health satisfaction improved significantly after intervention (p=0.0003 and p<0.0001, respectively). Mean scores on specific domains (physical health, psychological, social relationships, and environment) also significantly increased (p<0.001). Physical health showed the largest increase and psychological the smallest. As measured by modified KHQ, participants’ perception of their health improved significantly after intervention (p<0.0001) as did their perception of how much fistula affects their life (p<0.0001). The KHQ also assesses seven functional domains. Mean scores significantly increased in each after intervention (p<0.01). Conclusions: TERREWODE’s intervention was associated with significant positive changes in participants’ perception of and satisfaction with health and wellbeing. While many effects of incurable fistula cannot be eliminated, individualized support may mitigate QoL impacts. Such interventions may be adapted in other settings; standardized measures enable comparison of approaches.